Stand Corrected - Seet, Zhun Hao Dannie (2017)
This paper presents ‘Stand Corrected’, the first communication campaign in Singapore to raise awareness and educate young adults on ‘Text Neck’ syndrome, initiated by four final-year students from Wee Kim Wee School of Communication and Information, Nanyang Technological University. The campaign goal is to reduce the prevalence of long-term spinal complications, by having young adults aged 21 to 29 be mindful of their own posture while using mobile devices and to adopt lifestyle changes to curb ‘Text Neck’ syndrome. The paper summarises the primary and secondary research conducted to shape the campaign’s overall strategy, messaging, and tactics. A mix of qualitative and quantitative research was conducted to gather expert insights, and current perceived awareness and attitudes towards ‘Text Neck’. Drawing insights from our formative research, a three-phase campaign approach - engage, trigger and reinforce was developed as a framework for the campaign’s execution. The campaign strategy of creating an interactive experience helps to shed light on ‘Text Neck’ in an appealing and relatable way for young adults. A summary of specific tactics, both digital and on-ground is detailed in each of the three phases. The paper concludes with an evaluation of the campaign’s effectiveness through an analysis of the impact and output objectives, that includes analyzing a pre-and-post campaign survey, media coverages obtained, as well as testimonials from key stakeholders. A retention test was also conducted three weeks after the end of the campaign to assess campaign recall of key messages. Lastly, photos, correspondences, and collaterals that were used in the campaign execution can be found in the appendices of this paper.